2021
DOI: 10.1038/s41413-021-00152-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Lrp5 enhanced the anti-breast cancer effects of osteocytes in bone

Abstract: Osteocytes are the most abundant cells in bone, which is a frequent site of breast cancer metastasis. Here, we focused on Wnt signaling and evaluated tumor-osteocyte interactions. In animal experiments, mammary tumor cells were inoculated into the mammary fat pad and tibia. The role of Lrp5-mediated Wnt signaling was examined by overexpressing and silencing Lrp5 in osteocytes and establishing a conditional knockout mouse model. The results revealed that administration of osteocytes or their conditioned medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…In Wnt signaling, we observed that the overexpression of Wnt1 and Fzd7 did not generate iTS cells. In the generation of iTS cells from osteocytes, we have previously shown that the overexpression of β-catenin and Lrp5 but not Lrp6 promoted the anti-tumor capabilities and the protection of tumor-invased bone 1 . In osteocytes and MSCs, the overexpression of multiple pro-tumorigenic genes and the administration of tumor-promoting compounds have been shown to generate iTSC that significantly inhibited the progression of adjacent tumors 1 - 3 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Wnt signaling, we observed that the overexpression of Wnt1 and Fzd7 did not generate iTS cells. In the generation of iTS cells from osteocytes, we have previously shown that the overexpression of β-catenin and Lrp5 but not Lrp6 promoted the anti-tumor capabilities and the protection of tumor-invased bone 1 . In osteocytes and MSCs, the overexpression of multiple pro-tumorigenic genes and the administration of tumor-promoting compounds have been shown to generate iTSC that significantly inhibited the progression of adjacent tumors 1 - 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In the generation of iTS cells from osteocytes, we have previously shown that the overexpression of β-catenin and Lrp5 but not Lrp6 promoted the anti-tumor capabilities and the protection of tumor-invased bone 1 . In osteocytes and MSCs, the overexpression of multiple pro-tumorigenic genes and the administration of tumor-promoting compounds have been shown to generate iTSC that significantly inhibited the progression of adjacent tumors 1 - 3 . Further analyses are needed to elucidate the requirement for creating effective iTS CM from varing tumor and non-tumor cells, considering types of target cancer cells, as well as pathways and genes to be activated and overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations